Reading for learning - Nikolajeva, Maria (Benjamins Publ. Co., 2014)
How does reading fiction affect young people? How can they transfer fictional experience into real life? Why do they care about fictional characters? How does fiction enhance young people's sense of self-hood? Supported by cognitive psychology and brain research, this ground-breaking book is the first study of young readers' cognitive and emotional engagement with fiction. It explores how fiction stimulates perception, attention, imagination and other cognitive activity, and opens radically new ways of thinking about literature for young readers. Examining a wide range of texts for a young audience, from picturebooks to young adult novels, the combination of cognitive criticism and children’s literature theory also offers significant insights for literary studies beyond the scope of children’s fiction. An important milestone in cognitive criticism, the book provides convincing evidence that reading fiction is indispensable for young people’s intellectual, emotional and social maturation.
Bibliography p. 229-244
Keywords: Language awareness in children; Reading; Psychology of; Cognitive styles in children; Reading; Psychology and literature; Children's literature